Factors affecting antidepressant use by patients requiring home parenteral nutrition. Issue 1 (30th April 2021) - Cloutier, Anabelle; Deutsch, Liat; Miller, Bethany; Leahy, Gavin; Ablett, Joanne; Healey, Andrew; Twist, Katherine; Teubner, Antje; Abraham, Arun; Taylor, Michael; Pironi, Loris; Lal, Simon
Abstract: Background: Home parenteral nutrition (HPN) is a life‐saving therapy for patients with chronic intestinal failure but can be associated with a degree of psychological distress. The factors associated with the need for antidepressants (ADs) in this cohort have not yet been described. Methods: The study involved prospective data collection from patients attending an HPN clinic at a national intestinal failure referral center. Patients requiring HPN as a result of active malignancy were excluded. Patients were divided in 2 groups according to AD usage; demographic, anthropometric, socioeconomic characteristics, and intravenous supplementation (IVS) regimens were compared between groups. Results: A total of 184 patients were recruited between July 2018 and April 2019, with an overall prevalence of AD use of 41.7% (70/168 patients). Daily mean IVS volume was significantly higher among patients taking AD ("AD" group; 2125.48 ± 991.8 ml/day, "no‐AD" group; 1828.54 ± 847.0 ml/day, P = .039), with the proportion of patients needing high‐volume IVS (≥3000 ml/day) being 3 times higher in the AD group (20.0%(14/70 patients) vs 6.1% (6/98 patients), P = .006). The average energy IVS infusion per day was similar between the groups. Conclusion: This is the first study to demonstrate that AD use correlates with higher IVS volume rather than energy requirements in HPN patients, suggesting that high IVS volume requirements may be better associated with the patient's disease burden. Early and tailored mental health intervention may be beneficial in those with high IVS volume requirements.